Variabilidade pluviométrica na Mesorregião do Triângulo Mineiro/Alto Paranaíba - MG - Santos, Juliana Gonçalves (2015)
This study had for general objective to analyze the pluviometric variability of the Triangulo Mineiro/Alto Paranaíba mesoregion. To the accomplishment of this research was employed data provided by the National Water Agency (ANA) of 19 pluviometric stations located in the study area, comprising a historical series of 34 years (1980-2013). After the data has been tabulated, different methodologies were applied to verify the precipitation variability in the annual, seasonal, monthly and daily scales, with emphasis on statistical analysis, criteria and techniques to define the beginning and the end of the rainy season, methodologies for dry spells counting, geoprocessing tools, among others. The results showed that in the mesoregion the rain accumulates on average 1440 mm per year, occurring seasonally. The rainy season, which begins predominantly in October and ends in early April receives 85% of the total annual pluviosity, being December and January the rainiest months. The pluviometric events are concentrated, because approximately 50% of the precipitated volume occurs in rains with over of 30 mm daily. During the rainy season is common the occurrence of dry spells that are predominantly low to medium intensity, from 7 to 12 days, occurring mainly in the months of February and March. In the dry season, which receives only 15% of the annual pluviometric total, scarce rainfall occurs especially in the months of April and September, being the June, July and August quarter the driest of the year